Virtual Reality for Veteran Relaxation: Can VR Therapy Help Veterans Living With Dementia Who Exhibit Responsive Behaviors? - Appel, Lora; Appel, Eva; Kisonas, Erika; Lewis, Samantha; Sheng, Lacey Qing (Frontiers in Virtual Reality, 2022)
Background: Veterans with post-traumatic stress disorder are more likely to develop dementia and exhibit responsive behaviours such as physical and verbal aggressiveness (biting, cursing). In long-term care institutions, responsive behaviours are associated with high staff burnout, low engagement, and elevated risk of patient abuse/ neglect, in addition to poor clinical outcomes. Virtual Reality (VR) therapy is feasible, safe and acceptable for frail older adults with cognitive impairment. Perley Health is considering introducing VR-therapy as a non-pharmacological first-line of treatment to reduce responsive behaviours in residents with dementia. Objective: To evaluate the feasibility (acceptability, comfort) and potential benefits (enjoyment, relaxation, reducing pain, and managing responsive behaviours) of introducing VR-therapy for residents with dementia who exhibit responsive behaviours. Methods: Participants were recruited through convenience sampling into a prospective, longitudinal, non-randomized, interventional study at Perley Health, during 2019. VR-therapy consisted of watching 360°-VR footage (natural and social scenes) using Oculus-Go head-mounted-display. Sessions were either “scheduled” akin to other recreational activities, or “targeted” before or during activities/events expected to trigger responsive behaviours (e.g., bathing/toileting, sundowning, wound care). Baseline scores from validated tools and daily progress notes were collected from patients’ electronic records. Recreational therapists conducted quantitative surveys and qualitative structured-observations during the VR-therapy study sessions. Described are the changes implemented to data collection/ analyses as a number of methodological challenges arose during the study. Results: Thirty-three residents (avg. age=91.6) participated in 2 to 6 (avg=3.3) VR-therapy sessions per resident, totaling 111 sessions, of which 98 (88%) were scheduled and 13 (12%) were targeted. In 61% (68/111) of sessions, no responsive behaviours developed, and no sedating medications were administered during VR-therapy. The majority (63%, 70/111) of participants found the VR equipment comfortable, and in 47% (52/111) of VR-therapy sessions, the residents felt good or better than before the session. In 33% (37/111) of sessions, residents reminisced about the past and in 67% (74/111) of sessions residents reported wanting to try VR again. Conclusion: VR-therapy was acceptable and enjoyable for veterans with dementia. Perley Health continues to provide VR-therapy as a recreational tool beyond the study period. Future research should focus on reducing environmentally-triggered responsive behaviours.